2012
DOI: 10.1177/0194599812442612
|View full text |Cite
|
Sign up to set email alerts
|

Graduated Endoscopic Multiangle Approach for Access to the Infratemporal Fossa

Abstract: Endoscopic access to the ITF can be accomplished by each of the 4 methods described. A multiangle, graduated approach can provide surgeons the ability to customize surgical access depending on the location of a specific lesion within the ITF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 31 publications
0
54
0
1
Order By: Relevance
“…4,7,9,12,18,20,30,36 With this shift in surgical paradigms, the staging criteria used for JNA were revised by Snyderman et al 33 to place a higher emphasis on cranial base extension and remaining vascularity postembolization, characteristics they believed to be more predictive of morbidity and tumor recur- Currently, the most common approach to the ITF is the transcervical approach in a relaxed skin tension line, as it provides adequate access without poor cosmetic outcome and risk to the facial nerve. 8 This approach is not without limitations, as it is particularly challenging in tumors with great medial and superior extension. 8 The increased use of the endoscope has led to the development of techniques that could provide increased access to challenging areas of the skull base.…”
Section: Case 1: Ipsilateral Endoscopic Endonasal Approach (Uninostrimentioning
confidence: 99%
See 1 more Smart Citation
“…4,7,9,12,18,20,30,36 With this shift in surgical paradigms, the staging criteria used for JNA were revised by Snyderman et al 33 to place a higher emphasis on cranial base extension and remaining vascularity postembolization, characteristics they believed to be more predictive of morbidity and tumor recur- Currently, the most common approach to the ITF is the transcervical approach in a relaxed skin tension line, as it provides adequate access without poor cosmetic outcome and risk to the facial nerve. 8 This approach is not without limitations, as it is particularly challenging in tumors with great medial and superior extension. 8 The increased use of the endoscope has led to the development of techniques that could provide increased access to challenging areas of the skull base.…”
Section: Case 1: Ipsilateral Endoscopic Endonasal Approach (Uninostrimentioning
confidence: 99%
“…8 In this paper, we apply the principles of multicorridor surgery and describe a graduated multiangle, multicorridor approach for resection of complex JNAs. Four different surgical corridors (ipsilateral nostril, contralateral nostril, sublabial Caldwell-Luc maxillotomy, and transcranial) were used in various combinations in a stepwise fashion depending on the size and location of the JNA.…”
mentioning
confidence: 99%
“…In addition, we found that the transseptal approach has the least vertical working space; as a result, it may not be the best option in the case of tumors or lesions that extend in the same sagittal plane. The approaches we describe in this study were previously described with a detailed anatomical overview, 9,19 but an analysis of the exposed working space, including the surgical freedom and the area of exposure, has not been previously described. These concepts are important in planning the appropriate surgical approach for a specific lesion and for understanding the limitations of each of the approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Eloy et al concluded that adding this approach to any of the previously described approaches may lead to an increased surgical freedom for the superior portion of the infratemporal fossa. 19 With the increased experience of the surgical team, the use of angled endoscopes and angled instruments can be helpful in increasing the size of the accessible operative field and leading to improved tumor resections. 30,31 Although these angled instruments and endoscopes would greatly increase the extent and application for each approach, in our comparison we used only straight instruments and a 0-degree endoscope, so that we could study the approaches in a standard manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation